2019
DOI: 10.1016/j.eurox.2019.100023
|View full text |Cite
|
Sign up to set email alerts
|

Trend in cesarean delivery rate among twin pregnancies over a 20 years epoch and the accompanied maternal and perinatal outcomes

Abstract: Objective To examine the trend of cesarean delivery (CD) rate among twin pregnancies and the trend in maternal and neonatal morbidities within two decades. Study design Population-based cohort study, conducted at a single teaching hospital in Israel on data between January 1995 and December 2015. All pregnant women with twin gestation who delivered at a gestational age of 24 weeks or more were included. Data on mode of deliveries, Apgar score <7 at 5 min, cord artery pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…In our cohort, primary caesareans did not increase. Similarly to our results, the increasing caesarean rates in Israel were not combined with lower rates of Apgar score < 7 at 5 min or of PPH during this period [31].…”
Section: Meaning Of the Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…In our cohort, primary caesareans did not increase. Similarly to our results, the increasing caesarean rates in Israel were not combined with lower rates of Apgar score < 7 at 5 min or of PPH during this period [31].…”
Section: Meaning Of the Findingssupporting
confidence: 89%
“…In central Europe, the rates were 43.9% in the Netherlands, 54.8% in France and 74.8% in Germany. Studies considering changing rates over time were published from Israel, whereby the authors reported on a total increase of caesarean rates in twins from 43.4% in 1995 to 66.0% in 2015 with increasing numbers only in non-laboring women [31]. In our cohort, primary caesareans did not increase.…”
Section: Meaning Of the Findingsmentioning
confidence: 47%
“…First, it only included twin pregnancies delivered via cesarean section. Due to physician counseling and maternal requirements for selective cesarean section to avoid combined delivery, the cesarean delivery rate of twin pregnancies has increased dramatically ( 60 62 ). In our center, nearly 90% of women with twin pregnancies undergo a cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies show that the cesarean section rate is increasing globally. [1][2][3][4][5] Most of the literature and authorities accept a CS rate of 10-15%. If the CS rate is <10% then there is an increased chance of more maternal and neonatal mortality and morbidity due to less access to timely cesarean section facilities.…”
Section: Introductionmentioning
confidence: 99%